Graphene Microcapsule Arrays for Combinatorial Electron Microscopy and Spectroscopy in Liquids - Yulaev, Alexander (ACS Appl Mater Interfaces, 2017)
Atomic-scale thickness, molecular impermeability, low atomic number, and mechanical strength make graphene an ideal electron-transparent membrane for material characterization in liquids and gases with scanning electron microscopy and spectroscopy. Here, we present a novel sample platform made of an array of thousands of identical isolated graphene-capped micro-channels with high aspect ratio. A combination of a global wide field of view with high resolution local imaging of the array allows for high throughput in situ studies as well as for combinatorial screening of solutions, liquid interfaces and immersed samples. We demonstrate the capabilities of this platform by studying a pure water sample in comparison with alkali halide solutions, a model electrochemical plating process and beam induced crystal growth in liquid electrolyte. Spectroscopic characterization of liquid interfaces and immersed objects with Auger and X-ray fluorescence analysis through the graphene membrane are also demonstrated